THE ART OF POLITENESS: CULTURAL NUANCES IN ASIAN COUNTRIES (Ta'limning zamonaviy transformatsiyasi, 2024)
Explore the rich tapestry of politeness norms across various Asian countries in this illuminating article. From Japan's intricate balance between "tatemae" and "honne" to China's emphasis on preserving harmony, delve into the nuanced ways politeness is expressed. Discover the significance of honorific language in South Korea, the tradition of hospitality in India, and the concept of "kreng jai" in Thailand. Gain insights into cultural gestures, greetings, and language nuances that shape interpersonal interactions in Asia, and learn to navigate diverse cultural landscapes with grace and respect.